2016
DOI: 10.1128/jvi.01392-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Mapping of the Binding Sites and Structural Analysis of Kaposi's Sarcoma-Associated Herpesvirus Viral Interferon Regulatory Factor 2 Reveal that It Is a DNA-Binding Transcription Factor

Abstract: The oncogenic herpesvirus Kaposi's sarcoma-associated herpesvirus (KSHV) is known to encode four viral interferon regulatory factors (vIRF1 to -4) to subvert the host antiviral immune response, but their detailed DNA-binding profiles as transcription factors in the host remain uncharacterized. Here, we first performed genome-wide vIRF2-binding site mapping in the human genome using chromatin immunoprecipitation coupled with high-throughput sequencing (ChIP-seq). vIRF2 was capable of binding to the promoter reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…A comparison of the cellular transcriptome in KSHV.WT- and KSHV.ΔvIRF2-infected cells showed that, at protein levels found in KSHV-infected cells, vIRF2 is a transcriptional regulator of different cellular genes (Table 1). This is in line with the fact that it binds to different cellular promoter regions [36]. Among the cellular genes involved in host defense that are differentially expressed in KSHV.WT- vs. KSHV.ΔvIRF2-infected endothelial cells (Table 1), we could identify the IFN-induced proteins with tetratricopeptide repeats 1, 2 and 3 (IFIT1, 2 and 3), whose expression we could show to be directly or indirectly induced by vIRF2 (Fig 7) and which restrict KSHV lytic protein expression (Fig 8).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A comparison of the cellular transcriptome in KSHV.WT- and KSHV.ΔvIRF2-infected cells showed that, at protein levels found in KSHV-infected cells, vIRF2 is a transcriptional regulator of different cellular genes (Table 1). This is in line with the fact that it binds to different cellular promoter regions [36]. Among the cellular genes involved in host defense that are differentially expressed in KSHV.WT- vs. KSHV.ΔvIRF2-infected endothelial cells (Table 1), we could identify the IFN-induced proteins with tetratricopeptide repeats 1, 2 and 3 (IFIT1, 2 and 3), whose expression we could show to be directly or indirectly induced by vIRF2 (Fig 7) and which restrict KSHV lytic protein expression (Fig 8).…”
Section: Discussionsupporting
confidence: 67%
“…Expression of the spliced vIRF2 mRNA has previously been reported to occur only in the lytic replication cycle in different KSHV positive cell lines [26, 6568]. Recently, it was shown that vIRF2 is able to bind the promoter regions of different cellular genes by means of a DNA-binding domain (DBD; aa 7–114); a nuclear localization signal (aa146-159) has been identified at the N-terminal end of the vIRF2 protein [36, 69].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to vIRF1, genome-wide chromatin immunoprecipitation coupled with high-throughput sequencing (ChIP-Seq) analysis revealed that vIRF2 is able to bind the promoter regions of numerous cellular genes [45]. Notably, vIRF2 DBD (amino acid 7 to 144) was shown to bind to the promoter regions of PIK3C3, HMGCR, HMGCL and subsequently deregulated their expression levels [45]. Importantly, the consequence of such binding contributed to enhancement of KSHV infection and KSHV-associated pathogenesis.…”
Section: Virf2 (K11 and K111)mentioning
confidence: 99%
“…In breast cancer, HMGCL and other enzymes associated with ketone-body production were preferentially expressed in the tumor stroma 35 . The oncogenic Kaposi’s sarcoma-associated herpesvirus was shown to interfere with transcription of HMGCL directly by targeting its promoter region 36 .…”
Section: Introductionmentioning
confidence: 99%